The Impact of Growth and Development Stimulation Education on Parental Competence in Detecting Developmental Milestones in Children Aged 0–5 Years - Nadia Firzanly Basalama; Dwi Nur Octaviani Katili; St. Surya Indah Nurdin; Efri Leny Rauf (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Developmental stimulation refers to a series of activities aimed at promoting optimal growth and development in children. One of the factors influencing the success of child growth and development is the knowledge and ability of parents to detect early signs of development. This research aimed to determine the effect of developmental stimulation education on the early detection of developmental milestones in children aged 0-5 years. The research method was a pre-experimental design using a pretest-posttest one group design approach. The subjects included 73 samples, with 17 samples aged 0-12 months, 18 samples aged 12-36 months, and 38 samples aged 36-30 months. Early detection ability was measured before and after education using the KPSP questionnaire as a reference. The results indicated that in the 0-12 month age group, there was a significant increase in early detection ability after receiving education (p1 = 0.001, p < 0.05). In the 12-36 month age group, a significant improvement was also observed (p2 = 0.001, p < 0.05), while the 36-60 month age group showed an increase after education (p3 = 0.001, p < 0.05). this study concluded that there was a significant effect of developmental stimulation education on the early detection ability of parents for children aged 0-5 years.